1988
DOI: 10.1021/ac00170a014
|View full text |Cite
|
Sign up to set email alerts
|

Study of equilibria in 0.03 mM molybdate acidic aqueous solutions by factor analysis applied to ultraviolet spectra

Abstract: Support of this work by the National Science Foundation (Chemical Analysis Program, Grant CHE-8215508) and the North Carolina Board of Science and Technology (Grant 3125) is gratefully acknowledged. Thanks are also due to the Alcoa Foundation for providing an Alcoa Undergraduate Summer Research Fellowship to J.M.W. and to the R. J. Reynolds Foundation for providing a Wake Forest University Reynolds Research Leave Grant to W.L.H. A.I. was a 1983 participant in the Swedish CHUST Program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 49 publications
2
44
0
Order By: Relevance
“…The energetics of this reaction are described in more detail in a previous study (Tossell, 2005). Several previous researchers have suggested that the stable form of MoO 2 (OH) 2 , neutral molybdic acid, is actually Mo(OH) 6 or MoO 3 (OH 2 ) 3 , based on thermodynamic criteria (Cruywagen andHeyns, 1989, 2000) or analysis of the UV-vis spectra (Ozeki et al, 1988) and quantum calculation of this spectrum, using assumed geometries (Ozeki et al, 1996). However, we see for reaction 2 that the formation of the six-coordinate (roughly) octahedral Mo(OH) 6 molecule from MoO 2 (OH) 2 and two waters is calculated to be highly endoergic, indicating that the Mo(OH) 6 species is highly unstable.…”
Section: Calculation Of Stabilities Of Mo Complexesmentioning
confidence: 98%
“…The energetics of this reaction are described in more detail in a previous study (Tossell, 2005). Several previous researchers have suggested that the stable form of MoO 2 (OH) 2 , neutral molybdic acid, is actually Mo(OH) 6 or MoO 3 (OH 2 ) 3 , based on thermodynamic criteria (Cruywagen andHeyns, 1989, 2000) or analysis of the UV-vis spectra (Ozeki et al, 1988) and quantum calculation of this spectrum, using assumed geometries (Ozeki et al, 1996). However, we see for reaction 2 that the formation of the six-coordinate (roughly) octahedral Mo(OH) 6 molecule from MoO 2 (OH) 2 and two waters is calculated to be highly endoergic, indicating that the Mo(OH) 6 species is highly unstable.…”
Section: Calculation Of Stabilities Of Mo Complexesmentioning
confidence: 98%
“…MoO4 2-remained on the basis of the electrostatic interaction between MoO4 2-(Mo7O24 6-) and protonated acetylamide group of chitin film. 11 When the pH value of acetate buffer for accumulation of molybdenum was investigated (pH 3.3 -6.0), the peak current of molybdenum was maximum at pH 4.3. The reasons are as follows.…”
Section: Resultsmentioning
confidence: 99%
“…characterized the ultraviolet spectra of a similar aqueous molybdic acid solution. 62 Nelson et al devised an SMCR scheme using the SVD to resolve the spectra of pure components in mixtures. 63 They demonstrated the technique with the excitation-emission matrix of acridine, fluoranthene and pyrene.…”
Section: Isolation Of Pure Component Spectra From Mixturesmentioning
confidence: 99%